A single-cell map of peripheral alterations after FMT treatment in patients with systemic lupus erythematosus. Issue 135 (February 2023) - Zheng, Meiling; Zhou, Wenhui; Huang, Cancan; Hu, Zhi; Zhang, Bo; Lu, Qianjin; Zhao, Ming
Abstract: Systemic lupus erythematosus (SLE) is characterized by loss of self-tolerance and persistent self-aggression, sustained chronic inflammation, production of autoantibodies and multi-system damage, and is largely incurable to date. The gut microbiota and its metabolites, now recognized as crucial environmental triggers of local/systemic immune reactions, have been implicated in the development and progression of SLE. Fecal microbiota transplantation (FMT) is restoration of disturbed microbiota by transplanting foreign gut microbiota from healthy individuals into the gastrointestinal tract of diseased individuals. Our previous clinical trial suggests that FMT is a potentially safe and effective treatment for SLE. In order to elucidate the potential effect of FMT on peripheral immune cells of patients with SLE, we collected PBMCs (n = 30) of 13 SLE patients who participated in the clinical trial before and after the FMT-treatment, and performed single-cell RNA sequencing. The results first revealed that peripheral T lymphocytes of SLE patients decreased and NK cells increased after the FMT treatment. Then, sub-clustering analysis discovered that total CD4 + T cells highly expressed genes of IL7R, CD28, and CD8 + T cells highly expressed genes of GZMH and NKG7 after FMT treatment. Moreover, FMT treatment reduced the expression of interferon-related genes (IRGs) in CD4 + T, CD8 + T, DP, NK, and B cells of SLE patients. More importantly, interferon-related pathways were more enriched in cells of the FMT non-responder group, and further the interferon genes expression of lymphocytes and myeloid cells was negatively correlated with the efficiency of FMT treatment. Collectively, our data identified various immunophenotypic and associated gene set changes following FMT treatment, illustrating the heterogeneity of response to FMT treatment in SLE. Highlights: The expression of cytotoxic genes of GZMH and NKG7 was increased in CD8 + T cells of SLE patients after FMT treatment. FMT treatment reduced the expression of interferon-related genes (IRGs) in multiple immune cell types. The expression levels of interferon genes in lymphocyte and myeloid cells were negatively correlated with the efficiency of FMT treatment in SLE.